2017
DOI: 10.1016/j.peptides.2017.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Losartan counteracts the effects of cardiomyocyte swelling on glucose uptake and insulin receptor substrate-1 levels

Abstract: A growing body of evidence demonstrates an association between Angiotensin II (Ang II) receptor blockers (ARBs) and enhanced glucose metabolism during ischemic heart disease. Despite these encouraging results, the mechanisms responsible for these effects during ischemia remain poorly understood. In this study we investigated the influence of losartan, an AT1 receptor blocker, and secreted Ang II (sAng II) on glucose uptake and insulin receptor substrate (IRS-1) levels during cardiomyocyte swelling. H9c2 cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
(56 reference statements)
0
0
1
Order By: Relevance
“…Electrocardiogram analysis at P7 (after treatment) showed a mild acceleration of heart rate in mice treated with losartan or prazosin (Supplementary Figure S6B; Supplementary Table S3), as expected after vasodilator administration, and no significant changes in atrial conductance (P wave, PR interval) but a significantly shorter normalized QRS complex (Supplementary Figure S6B; Supplementary Table S3). Given that the in vitro effects reported for losartan and prazosin on metabolism, mitochondria, contractility or conductance of cardiomyocytes (Luo et al, 2001;Xu et al, 2009;Pennanen et al, 2014;Gerena et al, 2017) do not fully align with those we observed in vivo, our data suggest that treatment of neonatal mice with losartan or prazosin results in defective cardiac ventricular contractility and accelerated electrical conductivity, at least in part by affecting capillary pruning and cardiomyocyte maturation.…”
Section: Reduced Capillary Pruning By Losartan Delays Metabolic Switc...contrasting
confidence: 66%
“…Electrocardiogram analysis at P7 (after treatment) showed a mild acceleration of heart rate in mice treated with losartan or prazosin (Supplementary Figure S6B; Supplementary Table S3), as expected after vasodilator administration, and no significant changes in atrial conductance (P wave, PR interval) but a significantly shorter normalized QRS complex (Supplementary Figure S6B; Supplementary Table S3). Given that the in vitro effects reported for losartan and prazosin on metabolism, mitochondria, contractility or conductance of cardiomyocytes (Luo et al, 2001;Xu et al, 2009;Pennanen et al, 2014;Gerena et al, 2017) do not fully align with those we observed in vivo, our data suggest that treatment of neonatal mice with losartan or prazosin results in defective cardiac ventricular contractility and accelerated electrical conductivity, at least in part by affecting capillary pruning and cardiomyocyte maturation.…”
Section: Reduced Capillary Pruning By Losartan Delays Metabolic Switc...contrasting
confidence: 66%